PHENOTYPIC EVALUATION OF TOMATO GERMPLASM FOR THE SOURCE OF RESISTANCE AGAINST TOMATO LEAF CURL VIRUS DISEASE - M. A. Zeshan; M.A. Khan; S. Ali; M. Arshad (Journal of Animal and Plant Sciences, 2016)
Tomato leaf curl virus (TLCV) is the most devastating virus of tomato crop. TLCV is transmitted by whitefly (Bemisia tabaci) in a persistent and circulative manner. For the management of this problem, twenty seven tomato varieties/lines were screened for the source of resistance against tomato leaf curl virus disease (TLCVD) in field trial because no viricide was available to combat the viral diseases and insect vectors had developed resistance against the insecticides. The observations of TLCVD incidence were recorded on weekly basis. Varieties/lines were evaluated on the basis of symptomology. Grafting and whitefly mediated inoculation techniques were adopted to confirm the virus. Out of twenty seven varieties/lines, three were highly susceptible, six were susceptible, four were moderately susceptible, six were moderately resistant and eight cultivars were resistant. No variety/line was highly resistant or immune against TLCVD. Resistant genotypes (varieties/lines) can be used in breeding programs as an eco-friendly management approach.
Keywords: TLCV; Resistance; Incidence; Evaluation